/- Copyright (c) 2014 Jeremy Avigad. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Module: algebra.group Authors: Jeremy Avigad, Leonardo de Moura Various multiplicative and additive structures. Partially modeled on Isabelle's library. -/ import logic.eq data.unit data.sigma data.prod import algebra.function algebra.binary open eq eq.ops -- note: ⁻¹ will be overloaded open binary namespace algebra variable {A : Type} /- overloaded symbols -/ structure has_mul [class] (A : Type) := (mul : A → A → A) structure has_add [class] (A : Type) := (add : A → A → A) structure has_one [class] (A : Type) := (one : A) structure has_zero [class] (A : Type) := (zero : A) structure has_inv [class] (A : Type) := (inv : A → A) structure has_neg [class] (A : Type) := (neg : A → A) infixl `*` := has_mul.mul infixl `+` := has_add.add postfix `⁻¹` := has_inv.inv prefix `-` := has_neg.neg notation 1 := !has_one.one notation 0 := !has_zero.zero /- semigroup -/ structure semigroup [class] (A : Type) extends has_mul A := (mul_assoc : ∀a b c, mul (mul a b) c = mul a (mul b c)) theorem mul.assoc [s : semigroup A] (a b c : A) : a * b * c = a * (b * c) := !semigroup.mul_assoc structure comm_semigroup [class] (A : Type) extends semigroup A := (mul_comm : ∀a b, mul a b = mul b a) theorem mul.comm [s : comm_semigroup A] (a b : A) : a * b = b * a := !comm_semigroup.mul_comm theorem mul.left_comm [s : comm_semigroup A] (a b c : A) : a * (b * c) = b * (a * c) := binary.left_comm (@mul.comm A s) (@mul.assoc A s) a b c theorem mul.right_comm [s : comm_semigroup A] (a b c : A) : (a * b) * c = (a * c) * b := binary.right_comm (@mul.comm A s) (@mul.assoc A s) a b c structure left_cancel_semigroup [class] (A : Type) extends semigroup A := (mul_left_cancel : ∀a b c, mul a b = mul a c → b = c) theorem mul.left_cancel [s : left_cancel_semigroup A] {a b c : A} : a * b = a * c → b = c := !left_cancel_semigroup.mul_left_cancel structure right_cancel_semigroup [class] (A : Type) extends semigroup A := (mul_right_cancel : ∀a b c, mul a b = mul c b → a = c) theorem mul.right_cancel [s : right_cancel_semigroup A] {a b c : A} : a * b = c * b → a = c := !right_cancel_semigroup.mul_right_cancel /- additive semigroup -/ structure add_semigroup [class] (A : Type) extends has_add A := (add_assoc : ∀a b c, add (add a b) c = add a (add b c)) theorem add.assoc [s : add_semigroup A] (a b c : A) : a + b + c = a + (b + c) := !add_semigroup.add_assoc structure add_comm_semigroup [class] (A : Type) extends add_semigroup A := (add_comm : ∀a b, add a b = add b a) theorem add.comm [s : add_comm_semigroup A] (a b : A) : a + b = b + a := !add_comm_semigroup.add_comm theorem add.left_comm [s : add_comm_semigroup A] (a b c : A) : a + (b + c) = b + (a + c) := binary.left_comm (@add.comm A s) (@add.assoc A s) a b c theorem add.right_comm [s : add_comm_semigroup A] (a b c : A) : (a + b) + c = (a + c) + b := binary.right_comm (@add.comm A s) (@add.assoc A s) a b c structure add_left_cancel_semigroup [class] (A : Type) extends add_semigroup A := (add_left_cancel : ∀a b c, add a b = add a c → b = c) theorem add.left_cancel [s : add_left_cancel_semigroup A] {a b c : A} : a + b = a + c → b = c := !add_left_cancel_semigroup.add_left_cancel structure add_right_cancel_semigroup [class] (A : Type) extends add_semigroup A := (add_right_cancel : ∀a b c, add a b = add c b → a = c) theorem add.right_cancel [s : add_right_cancel_semigroup A] {a b c : A} : a + b = c + b → a = c := !add_right_cancel_semigroup.add_right_cancel /- monoid -/ structure monoid [class] (A : Type) extends semigroup A, has_one A := (one_mul : ∀a, mul one a = a) (mul_one : ∀a, mul a one = a) theorem one_mul [s : monoid A] (a : A) : 1 * a = a := !monoid.one_mul theorem mul_one [s : monoid A] (a : A) : a * 1 = a := !monoid.mul_one structure comm_monoid [class] (A : Type) extends monoid A, comm_semigroup A /- additive monoid -/ structure add_monoid [class] (A : Type) extends add_semigroup A, has_zero A := (zero_add : ∀a, add zero a = a) (add_zero : ∀a, add a zero = a) theorem zero_add [s : add_monoid A] (a : A) : 0 + a = a := !add_monoid.zero_add theorem add_zero [s : add_monoid A] (a : A) : a + 0 = a := !add_monoid.add_zero structure add_comm_monoid [class] (A : Type) extends add_monoid A, add_comm_semigroup A /- group -/ structure group [class] (A : Type) extends monoid A, has_inv A := (mul_left_inv : ∀a, mul (inv a) a = one) -- Note: with more work, we could derive the axiom one_mul section group variable [s : group A] include s theorem mul.left_inv (a : A) : a⁻¹ * a = 1 := !group.mul_left_inv theorem inv_mul_cancel_left (a b : A) : a⁻¹ * (a * b) = b := by rewrite [-mul.assoc, mul.left_inv, one_mul] theorem inv_mul_cancel_right (a b : A) : a * b⁻¹ * b = a := by rewrite [mul.assoc, mul.left_inv, mul_one] theorem inv_eq_of_mul_eq_one {a b : A} (H : a * b = 1) : a⁻¹ = b := by rewrite [-mul_one a⁻¹, -H, inv_mul_cancel_left] theorem inv_one : 1⁻¹ = 1 := inv_eq_of_mul_eq_one (one_mul 1) theorem inv_inv (a : A) : (a⁻¹)⁻¹ = a := inv_eq_of_mul_eq_one (mul.left_inv a) theorem inv.inj {a b : A} (H : a⁻¹ = b⁻¹) : a = b := by rewrite [-inv_inv, H, inv_inv] theorem inv_eq_inv_iff_eq (a b : A) : a⁻¹ = b⁻¹ ↔ a = b := iff.intro (assume H, inv.inj H) (assume H, congr_arg _ H) theorem inv_eq_one_iff_eq_one (a b : A) : a⁻¹ = 1 ↔ a = 1 := inv_one ▸ inv_eq_inv_iff_eq a 1 theorem eq_inv_of_eq_inv {a b : A} (H : a = b⁻¹) : b = a⁻¹ := by rewrite [H, inv_inv] theorem eq_inv_iff_eq_inv (a b : A) : a = b⁻¹ ↔ b = a⁻¹ := iff.intro !eq_inv_of_eq_inv !eq_inv_of_eq_inv theorem mul.right_inv (a : A) : a * a⁻¹ = 1 := calc a * a⁻¹ = (a⁻¹)⁻¹ * a⁻¹ : inv_inv ... = 1 : mul.left_inv theorem mul_inv_cancel_left (a b : A) : a * (a⁻¹ * b) = b := calc a * (a⁻¹ * b) = a * a⁻¹ * b : by rewrite mul.assoc ... = 1 * b : mul.right_inv ... = b : one_mul theorem mul_inv_cancel_right (a b : A) : a * b * b⁻¹ = a := calc a * b * b⁻¹ = a * (b * b⁻¹) : mul.assoc ... = a * 1 : mul.right_inv ... = a : mul_one theorem inv_mul (a b : A) : (a * b)⁻¹ = b⁻¹ * a⁻¹ := inv_eq_of_mul_eq_one (calc a * b * (b⁻¹ * a⁻¹) = a * (b * (b⁻¹ * a⁻¹)) : mul.assoc ... = a * a⁻¹ : mul_inv_cancel_left ... = 1 : mul.right_inv) theorem eq_of_mul_inv_eq_one {a b : A} (H : a * b⁻¹ = 1) : a = b := calc a = a * b⁻¹ * b : by rewrite inv_mul_cancel_right ... = 1 * b : H ... = b : one_mul theorem eq_mul_inv_of_mul_eq {a b c : A} (H : a * c = b) : a = b * c⁻¹ := by rewrite [-H, mul_inv_cancel_right] theorem eq_inv_mul_of_mul_eq {a b c : A} (H : b * a = c) : a = b⁻¹ * c := by rewrite [-H, inv_mul_cancel_left] theorem inv_mul_eq_of_eq_mul {a b c : A} (H : b = a * c) : a⁻¹ * b = c := by rewrite [H, inv_mul_cancel_left] theorem mul_inv_eq_of_eq_mul {a b c : A} (H : a = c * b) : a * b⁻¹ = c := by rewrite [H, mul_inv_cancel_right] theorem eq_mul_of_mul_inv_eq {a b c : A} (H : a * c⁻¹ = b) : a = b * c := !inv_inv ▸ (eq_mul_inv_of_mul_eq H) theorem eq_mul_of_inv_mul_eq {a b c : A} (H : b⁻¹ * a = c) : a = b * c := !inv_inv ▸ (eq_inv_mul_of_mul_eq H) theorem mul_eq_of_eq_inv_mul {a b c : A} (H : b = a⁻¹ * c) : a * b = c := !inv_inv ▸ (inv_mul_eq_of_eq_mul H) theorem mul_eq_of_eq_mul_inv {a b c : A} (H : a = c * b⁻¹) : a * b = c := !inv_inv ▸ (mul_inv_eq_of_eq_mul H) theorem mul_eq_iff_eq_inv_mul (a b c : A) : a * b = c ↔ b = a⁻¹ * c := iff.intro eq_inv_mul_of_mul_eq mul_eq_of_eq_inv_mul theorem mul_eq_iff_eq_mul_inv (a b c : A) : a * b = c ↔ a = c * b⁻¹ := iff.intro eq_mul_inv_of_mul_eq mul_eq_of_eq_mul_inv theorem mul_left_cancel {a b c : A} (H : a * b = a * c) : b = c := by rewrite [-inv_mul_cancel_left a b, H, inv_mul_cancel_left] theorem mul_right_cancel {a b c : A} (H : a * b = c * b) : a = c := by rewrite [-mul_inv_cancel_right a b, H, mul_inv_cancel_right] definition group.to_left_cancel_semigroup [instance] [coercion] [reducible] : left_cancel_semigroup A := ⦃ left_cancel_semigroup, s, mul_left_cancel := @mul_left_cancel A s ⦄ definition group.to_right_cancel_semigroup [instance] [coercion] [reducible] : right_cancel_semigroup A := ⦃ right_cancel_semigroup, s, mul_right_cancel := @mul_right_cancel A s ⦄ end group structure comm_group [class] (A : Type) extends group A, comm_monoid A /- additive group -/ structure add_group [class] (A : Type) extends add_monoid A, has_neg A := (add_left_inv : ∀a, add (neg a) a = zero) section add_group variables [s : add_group A] include s theorem add.left_inv (a : A) : -a + a = 0 := !add_group.add_left_inv theorem neg_add_cancel_left (a b : A) : -a + (a + b) = b := by rewrite [-add.assoc, add.left_inv, zero_add] theorem neg_add_cancel_right (a b : A) : a + -b + b = a := by rewrite [add.assoc, add.left_inv, add_zero] theorem neg_eq_of_add_eq_zero {a b : A} (H : a + b = 0) : -a = b := by rewrite [-add_zero, -H, neg_add_cancel_left] theorem neg_zero : -0 = 0 := neg_eq_of_add_eq_zero (zero_add 0) theorem neg_neg (a : A) : -(-a) = a := neg_eq_of_add_eq_zero (add.left_inv a) theorem eq_neg_of_add_eq_zero {a b : A} (H : a + b = 0) : a = -b := by rewrite [-neg_eq_of_add_eq_zero H, neg_neg] theorem neg.inj {a b : A} (H : -a = -b) : a = b := calc a = -(-a) : neg_neg ... = b : neg_eq_of_add_eq_zero (H⁻¹ ▸ (add.left_inv _)) theorem neg_eq_neg_iff_eq (a b : A) : -a = -b ↔ a = b := iff.intro (assume H, neg.inj H) (assume H, congr_arg _ H) theorem neg_eq_zero_iff_eq_zero (a : A) : -a = 0 ↔ a = 0 := neg_zero ▸ !neg_eq_neg_iff_eq theorem eq_neg_of_eq_neg {a b : A} (H : a = -b) : b = -a := H⁻¹ ▸ (neg_neg b)⁻¹ theorem eq_neg_iff_eq_neg (a b : A) : a = -b ↔ b = -a := iff.intro !eq_neg_of_eq_neg !eq_neg_of_eq_neg theorem add.right_inv (a : A) : a + -a = 0 := calc a + -a = -(-a) + -a : neg_neg ... = 0 : add.left_inv theorem add_neg_cancel_left (a b : A) : a + (-a + b) = b := by rewrite [-add.assoc, add.right_inv, zero_add] theorem add_neg_cancel_right (a b : A) : a + b + -b = a := by rewrite [add.assoc, add.right_inv, add_zero] theorem neg_add_rev (a b : A) : -(a + b) = -b + -a := neg_eq_of_add_eq_zero begin rewrite [add.assoc, add_neg_cancel_left, add.right_inv] end -- TODO: delete these in favor of sub rules? theorem eq_add_neg_of_add_eq {a b c : A} (H : a + c = b) : a = b + -c := H ▸ !add_neg_cancel_right⁻¹ theorem eq_neg_add_of_add_eq {a b c : A} (H : b + a = c) : a = -b + c := H ▸ !neg_add_cancel_left⁻¹ theorem neg_add_eq_of_eq_add {a b c : A} (H : b = a + c) : -a + b = c := H⁻¹ ▸ !neg_add_cancel_left theorem add_neg_eq_of_eq_add {a b c : A} (H : a = c + b) : a + -b = c := H⁻¹ ▸ !add_neg_cancel_right theorem eq_add_of_add_neg_eq {a b c : A} (H : a + -c = b) : a = b + c := !neg_neg ▸ (eq_add_neg_of_add_eq H) theorem eq_add_of_neg_add_eq {a b c : A} (H : -b + a = c) : a = b + c := !neg_neg ▸ (eq_neg_add_of_add_eq H) theorem add_eq_of_eq_neg_add {a b c : A} (H : b = -a + c) : a + b = c := !neg_neg ▸ (neg_add_eq_of_eq_add H) theorem add_eq_of_eq_add_neg {a b c : A} (H : a = c + -b) : a + b = c := !neg_neg ▸ (add_neg_eq_of_eq_add H) theorem add_eq_iff_eq_neg_add (a b c : A) : a + b = c ↔ b = -a + c := iff.intro eq_neg_add_of_add_eq add_eq_of_eq_neg_add theorem add_eq_iff_eq_add_neg (a b c : A) : a + b = c ↔ a = c + -b := iff.intro eq_add_neg_of_add_eq add_eq_of_eq_add_neg theorem add_left_cancel {a b c : A} (H : a + b = a + c) : b = c := calc b = -a + (a + b) : !neg_add_cancel_left⁻¹ ... = -a + (a + c) : H ... = c : neg_add_cancel_left theorem add_right_cancel {a b c : A} (H : a + b = c + b) : a = c := calc a = (a + b) + -b : !add_neg_cancel_right⁻¹ ... = (c + b) + -b : H ... = c : add_neg_cancel_right definition add_group.to_left_cancel_semigroup [instance] [coercion] [reducible] : add_left_cancel_semigroup A := ⦃ add_left_cancel_semigroup, s, add_left_cancel := @add_left_cancel A s ⦄ definition add_group.to_add_right_cancel_semigroup [instance] [coercion] [reducible] : add_right_cancel_semigroup A := ⦃ add_right_cancel_semigroup, s, add_right_cancel := @add_right_cancel A s ⦄ /- sub -/ -- TODO: derive corresponding facts for div in a field definition sub [reducible] (a b : A) : A := a + -b infix `-` := sub theorem sub_eq_add_neg (a b : A) : a - b = a + -b := rfl theorem sub_self (a : A) : a - a = 0 := !add.right_inv theorem sub_add_cancel (a b : A) : a - b + b = a := !neg_add_cancel_right theorem add_sub_cancel (a b : A) : a + b - b = a := !add_neg_cancel_right theorem eq_of_sub_eq_zero {a b : A} (H : a - b = 0) : a = b := calc a = (a - b) + b : !sub_add_cancel⁻¹ ... = 0 + b : H ... = b : zero_add theorem eq_iff_sub_eq_zero (a b : A) : a = b ↔ a - b = 0 := iff.intro (assume H, H ▸ !sub_self) (assume H, eq_of_sub_eq_zero H) theorem zero_sub (a : A) : 0 - a = -a := !zero_add theorem sub_zero (a : A) : a - 0 = a := subst (eq.symm neg_zero) !add_zero theorem sub_neg_eq_add (a b : A) : a - (-b) = a + b := !neg_neg ▸ rfl theorem neg_sub (a b : A) : -(a - b) = b - a := neg_eq_of_add_eq_zero (calc a - b + (b - a) = a - b + b - a : by rewrite -add.assoc ... = a - a : sub_add_cancel ... = 0 : sub_self) theorem add_sub (a b c : A) : a + (b - c) = a + b - c := !add.assoc⁻¹ theorem sub_add_eq_sub_sub_swap (a b c : A) : a - (b + c) = a - c - b := calc a - (b + c) = a + (-c - b) : neg_add_rev ... = a - c - b : by rewrite add.assoc theorem sub_eq_iff_eq_add (a b c : A) : a - b = c ↔ a = c + b := iff.intro (assume H, eq_add_of_add_neg_eq H) (assume H, add_neg_eq_of_eq_add H) theorem eq_sub_iff_add_eq (a b c : A) : a = b - c ↔ a + c = b := iff.intro (assume H, add_eq_of_eq_add_neg H) (assume H, eq_add_neg_of_add_eq H) theorem eq_iff_eq_of_sub_eq_sub {a b c d : A} (H : a - b = c - d) : a = b ↔ c = d := calc a = b ↔ a - b = 0 : eq_iff_sub_eq_zero ... = (c - d = 0) : H ... ↔ c = d : iff.symm (eq_iff_sub_eq_zero c d) theorem eq_sub_of_add_eq {a b c : A} (H : a + c = b) : a = b - c := !eq_add_neg_of_add_eq H theorem sub_eq_of_eq_add {a b c : A} (H : a = c + b) : a - b = c := !add_neg_eq_of_eq_add H theorem eq_add_of_sub_eq {a b c : A} (H : a - c = b) : a = b + c := eq_add_of_add_neg_eq H theorem add_eq_of_eq_sub {a b c : A} (H : a = c - b) : a + b = c := add_eq_of_eq_add_neg H end add_group structure add_comm_group [class] (A : Type) extends add_group A, add_comm_monoid A section add_comm_group variable [s : add_comm_group A] include s theorem sub_add_eq_sub_sub (a b c : A) : a - (b + c) = a - b - c := !add.comm ▸ !sub_add_eq_sub_sub_swap theorem neg_add_eq_sub (a b : A) : -a + b = b - a := !add.comm theorem neg_add (a b : A) : -(a + b) = -a + -b := add.comm (-b) (-a) ▸ neg_add_rev a b theorem sub_add_eq_add_sub (a b c : A) : a - b + c = a + c - b := !add.right_comm theorem sub_sub (a b c : A) : a - b - c = a - (b + c) := by rewrite [▸ a + -b + -c = _, add.assoc, -neg_add] theorem add_sub_add_left_eq_sub (a b c : A) : (c + a) - (c + b) = a - b := by rewrite [sub_add_eq_sub_sub, (add.comm c a), add_sub_cancel] theorem eq_sub_of_add_eq' {a b c : A} (H : c + a = b) : a = b - c := !eq_sub_of_add_eq (!add.comm ▸ H) theorem sub_eq_of_eq_add' {a b c : A} (H : a = b + c) : a - b = c := !sub_eq_of_eq_add (!add.comm ▸ H) theorem eq_add_of_sub_eq' {a b c : A} (H : a - b = c) : a = b + c := !add.comm ▸ eq_add_of_sub_eq H theorem add_eq_of_eq_sub' {a b c : A} (H : b = c - a) : a + b = c := !add.comm ▸ add_eq_of_eq_sub H end add_comm_group end algebra